AN ANALYSIS OF ENGLISH TEXTBOOK FOR ELEVENTH YEAR STUDENTS OF SENIOR HIGH SCHOOL ON THE BASIS OF THE 2013 CURRICULUM - Solikhah, Umi (MAGISTRA, 2016)
This article presents the results of the research about an Analysis of English Textbook forEleventh Year Students of Senior High School on the Basis of the 2013 Curriculum. The research was qualitativeresearch with descriptive method as the proper method. The object of the research was an English textbook foreleventh year students of Senior High School based on the 2013 Curriculum, with the title Bahasa InggrisKelas XI SMA/MA/SMK/MAK Semester 1, published by The Ministry of Education and Culture of Indonesia.The data of this research are the textbook contents, the approach and methods available on the Englishtextbook. The researcher uses a documentary analysis as the technique of collecting the data. For the techniqueof analyzing the data, the researcher uses the descriptive analysis to interpret the data. In giving the percentage,the researcher uses âCriterion Referenced Evaluationâ to percentage how far the textbook develops the contentwhich suitable with criteria of the 2013 Curriculum textbook and to percentage how far the textbook appliesapproach and methods in the English textbook.The research findings reveal that from percentage of the data, that 100% of the textbook content meansthat this percentage belongs to very good category. It implies that the English Textbook follows the demand ofthe 2013 Curriculum. Besides, from precentage of approach and methods, that is 80%, it means that approachand methods suggested by the 2013 Curriculum which are developed on the English textbook are good enough.The approach and methods which are developed in the textbook are scientific approach, discovery learning,problem based learning, and project based learning.Key Words: English textbook, syllabus, 2013 Curriculum.